Analysis of Biomass Potential, Carbon Stock, Carbon Sequestration, Oxygen Production, and Value of Environmental Services CO2 Uptake in Three Types of Forests in Buton District, Southeast Sulawesi Province, Indonesia - Nare, La; Rahman, Fatchur; Novianti, Vivi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Global warming is a symptom of an increase in the average temperature of the earth's surface. Global warming is caused by the large concentration of greenhouse gases in the atmosphere. One of the biggest greenhouse gases contributing to global warming is carbon dioxide (CO2). Forest vegetation can absorb about 50% of total emissions through a sequestration process stored in biomass in all parts of the plant. The study aimed to determine the potential of biomass, carbon stocks, carbon sequestration, oxygen production, and the CO2 absorption value of environmental services in three types of ecosystems in Buton Regency, Southeast Sulawesi Province. Research sampling was conducted using purposive sampling techniques and roaming methods. Calculation of biomass potential, carbon stock, carbon sequestration, oxygen production, and environmental service value of CO2 uptake using an allometric formula The results of research on the biomass potential of mangrove forests, lambusango forests, and pine forests were respectively, 16,108.27 tons/ha, 84,693.72 tons/ha, and 14,273.98 tons/ha. The potential carbon stock is 8,054.13 tons/ha, 42,346.86 tons/ha, and 7,136.99 tons/ha. The carbon absorption potential is 29,558.67 tons/ha, 155,412.98 tons/ha, and 26,192.75 tons/ha. The potential oxygen production is 21,504.54 tons/ha, 113,066.12 tons/ha, and 19,055.76 tons/ha, while the value of environmental services CO2 absorption is 2,221,038,614.63 Rp/ha, 11,677,731,637.57 Rp/ha, and 1,968,123,759 Rp/ha.